Faculty of Letters and Languages Department of Foreign Languages - Benlaksir, Faiza (Journal of Human Sciences, 2019)
The dialect of Constantine is the one spoken in the region of Constantine, situated in the eastern side of Algeria. It is unstandardised and considered as an under-resource language. The aim of this paper is to describe the direct and indirect loan words’ origins of the linguistic system used on a daily basis by the population of the city of Constantine. A historical background of the city is provided to understand the features of its linguistic levels. The specificities of the language are described and exemplified. Using an etymological approach, the different lexical origins are highlighted. The emphasis is laid on the direct and indirect origins of its lexis.